1995
DOI: 10.1080/07352689509701924
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Nitrogen in Plant Physiology and Plant Nutrition

Abstract: Nitrogen (N) nutrition enhances metabolic processes that influences the physicochemical environment at the soilroot interface, modifies rhizosphere conditions, interferes with the uptake of cations and anions, and enhances or represses the activity of several enzyme systems. Also, it affects growth patterns, protein content, and protein quality of seeds. Ammonium (NHJ-N nutrition increases anion uptake, free amino-N/protein ratios, and acidity of root free space; it reduces carbohydrate levels in plant tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(29 citation statements)
references
References 220 publications
2
21
0
6
Order By: Relevance
“…O nitrato é prontamente absorvido e convertido por enzimas e, em contato com carboidratos, forma as amidas e aminoácidos, passando então da forma inorgânica para a orgânica (Fernandes & Rossiello, 1995). É um dos nutrientes mais extraídos do solo pela planta da cana, considerada de elevada eficiência fisiológica na utilização de nitrogênio (Silveira, 1985), por isso pouco responsiva à fertilização nitrogenada.…”
Section: Introductionunclassified
“…O nitrato é prontamente absorvido e convertido por enzimas e, em contato com carboidratos, forma as amidas e aminoácidos, passando então da forma inorgânica para a orgânica (Fernandes & Rossiello, 1995). É um dos nutrientes mais extraídos do solo pela planta da cana, considerada de elevada eficiência fisiológica na utilização de nitrogênio (Silveira, 1985), por isso pouco responsiva à fertilização nitrogenada.…”
Section: Introductionunclassified
“…De acordo com Fernandes & Rossiello (1995), o dossel de um pasto é considerado plenamente desenvolvido quando ocorre interceptação de 90 a 95% de luz incidente, como consequência do elevado perfilhamento e expansão da área foliar das plantas constituintes do ecossistema. Nas condições deste experimento, a interceptação de luz variou de 92,95% para a menor dose de N a 95,80%, para a maior dose de N. A penetração de luz diminui de maneira assintótica, em função dos níveis de N aplicados (Tabela 1).…”
Section: Resultsunclassified
“…Many studies, worldwide have shown t h a t c r o p N u p t a k e i s c o -r e g u l a t e d b y b o th soil N supply and biomass accumulation processes (Fernandes & Rossiello, 1995;Hikosaka, 2005;Lemaire et al, 2007).When water supply is non-limiting, both carbon and nitrogen capture and use processes are closely linked with one another by the development of leaf area and the pattern of intercepted radiation Giunta et al, 2009), since about half of leaf nitrogen is invested in photosynthetic proteins (Ghannoum et al, 2005;Hikosaka, 2005). Because of these interrelationships, we also consider the roles of N nutrition in the processes of interception and use of solar radiation by forage grasses.…”
Section: Cynodon Nlemfuensis (Dry Season) Cynodon Nlemfuensis (Rainy mentioning
confidence: 99%